CALCULATE THE ESTIMATED TANKER BERTHING TIME BASED ON THE AMOUNT OF ETHYLENE LOADED - Yudhiyono, Yudhiyono; M. Yusuf, M. Yusuf; sugiyanto, sugiyanto (Meteor STIP Marunda, 2023)
One of the problems that coauses dweling time remain high is the uncertainty of loading and unloading time also the time for documents processing. Impact this uncertainty is an additional cost being charged to ships by the authorities because of additional berthing time. Based on the berthing time report it is necessary to calculate the ideal time for processing document. Ship Document Processing include the clearence in document, processing document when the ship enter the port. Clearence out is processing document before the ship leave the port. Loading/Unloading proess includes of loading/unloading preparation. Loading/unloading preparation activities for Ethylene must be carried out by following appropriate procedures, this is because ethylene is volatile and flammable hazardous material. In fact Activities involving dangerous goods are regulated separately ini International Maritime Organisation Regulations.